The importance of project management in SMEs for the development of new products through E-Collaboration - Mohammadjafari, M.; Ahmed, S.; Md Dawal, S.Z.; Zayandehroodi, H. (2011)
The research in this paper seeks ways for manufacturing companies to accomplish projects in real time with less cost. This paper describes a new model using critical success factors of implementing projects in small- and medium-sized enterprises (SMEs). The factors in the conceptual model were identified in past studies and are validated from interviews with 20 project managers in the electronics industry in Iran. Several prior researches have suggested critical success factors for reducing time and cost in the development of a new product. These factors are related to design, product, planning and procurement. However, none of these studies has proposed a model that specifies practices that should be undertaken to facilitate the progression to reduce time and cost in developing new products in SMEs. Following this, a development of a new model will likely prove important to help SMEs to understand what is required in order to be an effective global organization in terms of reducing time and cost through electronic collaboration (E-collaboration) and project management. The concept and value of E-collaboration and project management, and its strengths and weakness on SMEs, is also explained.